A variable undecad repeat domain in cavin1 regulates caveola formation and stability. (18th July 2018) - Tillu, Vikas A; Lim, Ye‐Wheen; Kovtun, Oleksiy; Mureev, Sergey; Ferguson, Charles; Bastiani, Michele; McMahon, Kerrie‐Ann; Lo, Harriet P; Hall, Thomas E; Alexandrov, Kirill; Collins, Brett M; Parton, Robert G
Abstract: Caveolae are plasma membrane invaginations involved in transport, signalling and mechanical membrane sensing in metazoans. Their formation depends upon multiple interactions between membrane‐embedded caveolins, lipids and cytosolic cavin proteins. Of the four cavin family members, only cavin1 is strictly required for caveola formation. Here, we demonstrate that an eleven residue (undecad) repeat sequence (UC1) exclusive to cavin1 is essential for caveolar localization and promotes membrane remodelling through binding to phosphatidylserine. In the notochord of mechanically stimulated zebrafish embryos, the UC1 domain is required for caveolar stability and resistance to membrane stress. The number of undecad repeats in the cavin1 UC1 domain varies throughout evolution, and we find that an increased number also correlates with increased caveolar stability. Lastly, we show that the cavin1 UC1 domain induces dramatic remodelling of the plasma membrane when grafted into cavin2 suggesting an important role in membrane sculpting. Overall, our work defines a novel conserved cavin1 modular domain that controls caveolar assembly and stability. Synopsis: The cavin1 protein is required for formation of caveolae, but the underlying mechanisms remain unclear. This study shows that a unique undecad repeat domain in cavin1 (UC1) is conserved across evolution and plays an essential role in caveola formation. Cavin1 proteins possess highly conserved but variable numbers of undecad repeat sequences in their C‐terminus predicted to form a right‐handed coiled‐ coil. The UC1 domain is essential for caveola localization and assembly in cells and in vivo, and binds to phosphatidylserine. The number of undecad repeats correlates with the ability of caveolae to respond to membrane stretching. Abstract : The cavin1 protein is required for formation of caveolae, but the underlying mechanisms remain unclear. This study shows that a unique undecad repeat domain in cavin1 (UC1) is conserved across evolution and plays an essential role in caveola formation.